Community Empowerment Through Making Snacks as a Home-Scale Business to Improve Community Welfare During the Pandemic in Cipeujeuh Kulon Village - Siti Rokhmah; Siti Julaekha; Romlah; Yuni Tazkiyah; Siti Marwah; Tati Haryati; Dahlia Arum Wangi; Navila Amalia; Taib Maulana; Nanang Mardani (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2024)
The Community Service Lecture (KPM) aims to carry out the tridharma function of higher education for every IAI Bunga Bangsa Cirebon Lecturer. One of the tridharma is carrying out community service by "Community Empowerment through making pastel cakes, sumpia, Bintang, ladu, gapit, kecimpring, fish crackers, ketapang seeds, salted dumplings, sweet dumplings, sweet potato chips, kunti tofu, pepes tofu, as a business "Home Scale in Improving Welfare in CipejeuhKulon Village, Lemah Abang District, Cirebon Regency". The problems with this service are (1) This business has not been managed professionally so that the pastel cakes have not varied in terms of taste to make them more attractive (2) There has been no guidance from the relevant agencies, such as entrepreneurship training regarding processing pastel cakes as a home business, (3) The community constrained by capital and marketing access. The approach method in the program includes: (1) Demonstration, namely through presentations and demonstrations of making pastel cakes (2) Training to the community about entrepreneurship, (3) All program activities are accompanied by the implementing team. The results achieved in the KPM program are (1) Snack food products in packaged form and flavor variants (2) Scientific articles. To make it easier for the target community to understand, direct practice is carried out at each stage of making snacks. From the results of this demonstration, the target community can implement pastel cake processing as a home-scale business so that it can improve the economy of the community in Cipeujeuh Kulon Village, Lemah Abang, Cirebon Regency.